A comparison of genomic methods to assess DNA replication timing - Emily Wheeler; Leigh Mickelson-Young; Emily E. Wear; Mason Burroughs; Hank W. Bass; Lorenzo Concia; William F. Thompson; Linda Hanley-Bowdoin (Scientific Reports)
Abstract Replication timing (RT), the temporal order in which genomic regions replicate, is considered a functional feature of multiple cellular processes and chromatin organization. Two approaches to measure RT are the Repli-seq and DNA copy number (also called S/G1) methods. We previously adapted Repli-seq using 5-ethynyl-2’- deoxyuridine (EdU) pulse-labeling and bivariate flow sorting, and while the approach offers high resolution and exposes heterogeneity in timing, the S/G1 method is a simpler, faster and less resource-intensive assessment. Here we modified the S/G1 technique by using EdU labeling (EdU-S/G1) to facilitate better separation of replicating from non-replicating nuclei during flow sorting, which enables the collection of a more pure sample of G1-phase nuclei. When comparing the three methods we found that profiles from the S/G1 and EdU-S/G1 methods are highly correlated with each other and with Repli-seq profiles for early replication. We also found that the EdU-S/G1 approach offers a better representation of replication in early and late S phase than the conventional S/G1 method. However, the high reproducibility of RT profiles among all three methods indicates that considerations of cost and sample availability can drive the decision of which method to choose.